Improved Heat Recovery at Skoghall Mill - Pinch analysis with economic and technical considerations - Ekström, Linda (My University, 2002)
The pulp and paper industry has a large consumption of energy. It is therefore interesting to see if this use of energy can be decreased. This would mean less use of fuel and lower emissions to the atmosphere. This study has been undertaken as a case study at Skoghall Board Mill, where the possibilities for decreased use of live steam by increased internal heat exchanging have been investigated. As a tool Pinch Technology has been used. This is a tool that makes it easier to see where the system has heat and cooling demand and at which temperatures. Using this as a base, it is then possible to identify where the potential for more internal heat exchange is possible and as a result one can reduce the steam demand. The mill has two power boilers in addition to the recovery boiler, one oil boiler and one bark boiler. The bark boiler is fired with both bark from the mill’s own debarking and purchased bark. The oil boiler has the highest marginal operating costs, thus a reduced steam demand will decrease usage of the oil boiler. By identifying the pinch violations in the system one can identify potential measures for increasing internal heat exchanging. Four alternatives with different degrees of heat recovery have been identified. For these cases the investment costs have been calculated and the technical consequences considered. The calculations were carried out for winter operation. Two cases were considered for potential fuel savings: oil fuel and bark fuel. The results show that the use of live steam can be reduced by 10 to 20 MW. The pay back periods for these investments lie around one year when the saved fuel is oil. For the case with bark the pay back periods are approximately 2.5 to 4 years.
Keywords: Kemiteknik; Chemical Engineering